Radiation from a moving planar dipole layer: Patch potentials versus dynamical Casimir effect - Fosco, Cesar Daniel (2014)
We study the classical electromagnetic radiation due to the presence of a dipole layer on a plane that performs a bounded motion along its normal direction, to the first nontrivial order in the amplitude of that motion. We show that the total emitted power may be written in terms of the dipole layer autocorrelation function. We then apply the general expression for the emitted power to cases where the dipole layer models the presence of patch potentials, comparing the magnitude of the emitted radiation with that coming from the quantum vacuum in the presence of a moving perfect conductor (dynamical Casimir effect).